1964
DOI: 10.1172/jci105105
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Differential Secretion of Oxytocin and Vasopressin in Man*

Abstract: In the present study we have attempted to answer the question whether vasopressin and oxytocin are secreted together or independently. This subject has been a matter of controversy during the past 35 years. The great variety of methods used in measuring oxytocin and vasopressin activities, the variety of animal species studied, and the variety and magnitude of stimuli employed in different studies make it very difficult to compare results and to draw conclusions as to whether or not there may be independent re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1965
1965
1978
1978

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Peeters & Debackere (1963) reported that in well hydrated goats with normal milk yields, diuresis was inhibited only occasionally during milking. Gaitan, Cobo & Mizrachi (1964) did not observe inhibition of diuresis during suckling in twenty-four experiments on lactating women and advanced this result as an argument in favour of independent release of oxytocin and vasopressin. The most direct method of determining whether there is a simultaneous release when milk ejection occurs, is to assay both hormones in samples of blood collected during suckling.…”
Section: Introductionmentioning
confidence: 79%
“…Peeters & Debackere (1963) reported that in well hydrated goats with normal milk yields, diuresis was inhibited only occasionally during milking. Gaitan, Cobo & Mizrachi (1964) did not observe inhibition of diuresis during suckling in twenty-four experiments on lactating women and advanced this result as an argument in favour of independent release of oxytocin and vasopressin. The most direct method of determining whether there is a simultaneous release when milk ejection occurs, is to assay both hormones in samples of blood collected during suckling.…”
Section: Introductionmentioning
confidence: 79%
“…The view that hyperosmolality is a specific stimulus for arginine vasopressin (AVP) release has been challenged by studies showing increases in uterine or milkejecting activity in animals given intracarotid infusions of hypertonic saline (1)(2)(3). However, careful studies in man of the milk-ejecting or uterine responses to iv infusions of hypertonic saline have yielded conflicting results, possibly related in part to the lesser intensity of the osmotic stimulus (4)(5)(6)(7). A major shortcoming of such studies is that AVP possesses substantial intrinsic activity in either milk ejection or uterotonic assays making it difficult to determine with certainty whether or not oxytocin (OT) was actually released (8).…”
mentioning
confidence: 99%
“…In accord with the separate neurone hypothesis it was found that stimulation of localized areas of the hypothalamus with implanted electrodes could effect an independent release of vasopressin and o~y t o c i n .~*~~* '~~~~ Selective release of vasopressin has also been achieved by carotid occlusion19 and by hemorrhage.11*M*77 Oxytocin is released selectively during p a r t u r i t i~n~~ and by suck-ing14 and in lactating women under osmotic stress. 29 By application of biochemical subcellular fractionation methods t o bovinez0>M*6s and rabbit9 posterior pituitary homogenates, it was shown that a partial separation of oxytocin-and vasopressincontaining vesicles could be obtained on sucrose density gradients. These techniques were also used to obtain pinched-off nerve ending fractions ("neurosecretosomes") with different v a s e pressin/oxytocin ratios,13 and to obtain neurosecretory vesicle fractions from the ox, one of which showed a relative enrichment in oxytocin and neurophysin I and another in vasopressin and neurophysin ILmn Taken together, these biochemical, physiological, and morphological studies suggested that the two hormones were probably stored in separate neurones in HNS together with their respective neurophysins.…”
Section: Evidence For the Separate Neurone Hypothesismentioning
confidence: 99%